Knowledge@Wharton on building corporate value (John Wiley & Sons, 2002)
Modern Strategies for Building Corporate Value the Old-Fashioned Way. Regardless of the e-commerce initiatives your business has undertaken, it should be increasingly clear that you’ve barely scratched the surface. Knowledge@Wharton On Building Corporate Value takes you beneath the surface to reveal what the Internet can truly do for your business, then shows you how today’s most innovative firms are already doing it. Knowledge@Wharton On Building Corporate Value clearly explains how you can integrate the Internet into every aspect of your business as it reveals techniques for: Using Internet tools to create and manage enduring brands. Understanding and managing risks created by the Internet . Pursuing strategic alliances to support your company’s goals